PENJADWALAN PRODUKSI JOB SHOP DENGAN MENGGUNAKAN ALGORITMA TABU SEARCH PADA PT. XYZ - Rencus Siburian; Abadi Ginting (Departemen Teknik Industri Universitas Sumatera Utara, 2013)
The research was conducted at PT. XYZ which is a manufacturing company engaged in the manufacture of spare parts of screwpress and digester. The study was conducted only in the manufacture of spare parts of screwpress, namely protection nut, screw worm, cone guide, dismentling plate, cone, pin & coupling nut, strainer, extension shaft, intermediate gear, and flexible coupling. The flow pattern at PT. XYZ is job shop and produced by make to order, each product has a different process flow, sequence and timing of different processes, but through the facilities of the same engine, so may result in idle time on a machine and the accumulation of another job on the machine. PT. XYZ used production scheduling by FCFS rule that still result in a delay in the completion of orders and there was so much undone job because makespan values was too large. The purpose of this study was to minimize the makespan, namely the Tabu Search Algorithm. Results from this study is the reduction occurred from time to schedule company with Tabu Search Algorithm is from 141.22 hours or minutes become 132.14 8473.2 7928.4 hours or minutes. Relative Error shows that the savings obtained makespan between Tabu Search Algorithm with the method of company is 6.8715% and the value of Efficiency Index is 1.068715. It can be concluded that the Tabu Search Algorithm produces a smaller makespan than the company actual scheduling.